Graphical Authentication Using Enhanced Hybrid Graphical Authentication System - M.D. Fatehah; M.K. Wafa; Nor Badrul Anuar; Mohd Zalisham Jali (Medwell Journals, 2024)
The username/password combination is still the most widely used method albeit various user authentication techniques have been introduced. Numerous studies have been conducted to investigate the scheme and it could be summarized that despite it weaknesses, it is the most favorable scheme. Thus, to reduce the weakness, authenticating users with image or pictures (i.e., graphical password) is prop osed as one possible alternative as it was claimed that pictures were easy to remember, easy to use and has considerable security. This study presents a study carried out to investigate user's performance and feedback towards the use of hybrid graphical methods (i.e., combining two graphical methods) as a method of authentication. Initially, a survey was conducted to identify participants' drawing patterns as their secret using the paper-based method and then the graphical software prototype was developed and tested randomly by 30 participants and lastly a survey was conducted in order to identify the level of guessability (i.e., security perspective). Overall, test on the prototype showed positive results as participants enjoyed using it and able to register within tolerable time.